A influência da opção religiosa na acumulação de capital humano: um estudo exploratório - Anuatti-Neto, Francisco; Narita, Renata Del Tedesco (Estudos Econômicos (São Paulo), 2004)
This article explores Brazilian official statistics on religion, in particular 1980 and 1991 Census and 1988 PNAD special survey. It searches for stylized facts of economics of religion summarized in Iannaccone (1998). The papers main question is to test an empirical relation between the parents religious affiliation and the children performance at school. This relation may indicate the existence a causal relation between religion and families human capital accumulation. Results indicate that Brazilian data reproduces most of stylized facts and the existence of differences in children schooling among selected religious groups persist after controlling for socio-economic factors.